Bimbingan Teknis Transplantasi Spons Laut pada Masa Covid 19 sebagai Prospek Bahan Baku Farmasi - Oce Astuti Oce; La Sara; Wa Ode Intiyani Mangurana; Rahmadani Rahmadani; Ira Ira; Wa Nurgayah; Emiyarti Emiyarti; Muhammad Kholil Hidayat Abdillah; La Ode Khairum Mastu (Institut Pertanian Bogor, 2022)
Sponges are organisms associated with coral reefs and have potential as pharmaceutical raw materials. One of the problems is that most people are not aware of the importance of this ecosystem and still use fishing gear that is not environmentally friendly, this causes the coral reef ecosystem to also suffer damage. This community service aims to educate and provide technical guidance to the younger generation of Lalowaru Village about the benefits of sponges and how to transplant sea sponges. The youth group was chosen as the target because during this Covid-19 period the youth organization in Lalowaru Village, South Konawe Regency did not go to schools as usual, so this education can provide knowledge that can be applied in protecting the aquatic environment. The implementation method consists of two stages, namely the first stage of field observations including licensing with village officials and preliminary study interviews and the second stage of socialization and transplantation practices. The activity was carried out for two days with 10 participants. Measurement results were concluded through interviews from before carrying out activities and after service activities. The results of the training and mentoring activities show that all target audiences understand the benefits of sponges as pharmaceutical raw materials that can be developed, as well as transplantation techniques. This increase in the knowledge of the young generation of youth organizations occurred after technical guidance through this service.